Two-dimensional quaternion Fourier transform of type II and quaternion wavelet transform - Bahri, M.; Ashino, R.; Vaillancourt, R. (2012 International Conference on Wavelet Analysis and Pattern Recognition, 2012)
A two-dimensional quaternion Fourier transform (QFT) defined with the kernel e - i+j+k/√3 ω · x is proposed. Some fundamental properties, such as convolution theorem and Plancherel theorem are established. The wavelet transform is extended to quaternion algebra using the kernel of the QFT.